Compton Mackenzie - Young, Kenneth (Writers and Their Work Series., 1968)
Few writers have given greater enjoyment to their contemporaries than Sir Compton Mackenzie. Since his first novel, The Passionate Elopement, was published in 1911 he has written more than a hundred books covering so many different aspects of life - from cats to music and religion, from Greece to Prince Charlie - that his versatility has at times bemused and offended critics. He has travelled widely - he has a particularly affection for Greece where he.